Legal Argumentation for The Resolution of Joint Property Dispute Through Decisions of The Supreme Court of The Republic of Indonesia From a Justice Perspective - Muhammad Hizbullah; Zein Achyar; MHd Yadi Harahap (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Based on the Supreme Court’s annual reports from 2021 to 2023, there has been a significant increase in cassation-level cases involving joint property disputes. The number rose from 156 cases in 2021 (including remaining cases from 2020) to 167 in 2022, and further to 238 in 2023. This upward trend indicates growing dissatisfaction with the resolution of joint property cases in terms of justice and benefit for the disputing parties. This research aims to analyze the legal argumentation in resolving joint property disputes at the cassation level from a justice perspective, focusing on two Supreme Court decisions: Number 78/K/AK/2021 and Number 298/K/AK/2022. These decisions reveal contrasting interpretations of justice. In case 78/K/AK/2021, the division was 70% to the wife and 30% to the husband, differing from Article 97 of the Compilation of Islamic Law (KHI), which mandates equal distribution. Conversely, case 298/K/AK/2022 upheld a 50:50 division. The study uses a qualitative method with a normative juridical approach, analyzing Supreme Court jurisprudence, relevant positive law, and statutory provisions. Joint property division in Indonesia is governed by the Civil Code, Law No. 1 of 1974, customary law, and KHI, with varying approaches based on legal traditions and societal values. The findings suggest that legal interpretations should consider philosophical, juridical, and social dimensions. Therefore, justice in joint property division may require flexible proportions (e.g., 70:30), rather than a rigid 50:50 split, to reflect each party’s actual contributions and to uphold fairness and benefit for all parties involved.